1992
DOI: 10.1073/pnas.89.9.4192
|View full text |Cite
|
Sign up to set email alerts
|

The central distribution of a corticotropin-releasing factor (CRF)-binding protein predicts multiple sites and modes of interaction with CRF.

Abstract: In recent studies to clone and characterize genes coding for the corticotropin-releasing factor-binding protein (CRF-BP), analysis of the tissue distribution of the CRF-BP gene indicated a high level of expression in the rat brain. We have now characterized by immunohistochemical and hybridization histochemical means the cellular localization of CRF-BP protein and mRNA expression, respectively. Results from both approaches converged to indicate that CRF-BP is expressed predominantly in the cerebral cortex, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
203
0
5

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(223 citation statements)
references
References 21 publications
(24 reference statements)
15
203
0
5
Order By: Relevance
“…(ii) The distribution of CRF2 receptor mRNA shows a unique highly localized distribution in the brain, with prominant expression in the limbic regions. This is in contrast to CRF1 receptor (14) or the CRF-binding protein (28), which are both widely and somewhat codistributed throughout the brain, particularly in cerebral cortex and in pituitary. In accordance with these findings, it can be hypothesized that different aspects of CRF physiology may be altered by drugs displaying selectivity for CRF1 vs. CRF2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) The distribution of CRF2 receptor mRNA shows a unique highly localized distribution in the brain, with prominant expression in the limbic regions. This is in contrast to CRF1 receptor (14) or the CRF-binding protein (28), which are both widely and somewhat codistributed throughout the brain, particularly in cerebral cortex and in pituitary. In accordance with these findings, it can be hypothesized that different aspects of CRF physiology may be altered by drugs displaying selectivity for CRF1 vs. CRF2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Autoradiography and radioligand binding studies during early postnatal life in the rat have demonstrated changes in receptor number and regional distribution [5,6,11,12,15]. The two methods have yielded conflicting information regarding CRH receptor distribution in a number of brain regions [12,16,17]. A potential basis for this discrepancy derives from CRH binding protein which may interact with the CRH ligand [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…The two methods have yielded conflicting information regarding CRH receptor distribution in a number of brain regions [12,16,17]. A potential basis for this discrepancy derives from CRH binding protein which may interact with the CRH ligand [12,16]. Binding studies may also provide limited information on the actual site of receptor synthesis because ligands may bind to neural receptors on cell bodies and along dendrites and axons [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies favor the involvement of CRF 2 receptors in regulating DRN functions, especially in the more caudal regions of the DRN (Hammack et al, 2003, Staub et al, 2006. Additionally, CRF binding protein (CRF-BP) has been reported to modulate the availability of CRF family peptides (Potter et al, 1992, Seasholtz et al, 2002. oCRF and rat UCNII may have different affinities for CRF-BP.…”
mentioning
confidence: 99%
“…Unfortunately, our results do not provide strong evidence to favor the role of one CRF receptor over another in their actions on serotonergic neurons and behavior described in this paper. Furthermore, CRF binding protein is present in the DRN and could modulate the availability of CRF family neuropeptides there (Potter et al, 1992, Seasholtz et al, 2002 thus altering local peptide concentrations. More specific pharmacologic and transgenic experiments should help clarify the roles of each receptor type as well as CRF-BP in the DRN.…”
mentioning
confidence: 99%